2022
DOI: 10.1108/ijse-06-2020-0384
|View full text |Cite
|
Sign up to set email alerts
|

The effect of international remittances on labour supply in Jordan: an empirical investigation

Abstract: PurposeThe purpose of the current study is to examine the effect of international remittances on the labour market participation of women and men left behind in Jordan. The study particularly focuses on the labour supply side for both women and men.Design/methodology/approachThe study draws on micro-data from the Jordan Labour Market Panel Survey (JLMPS) in 2010, a nationally representative survey, and addresses the endogeneity of receiving remittances through an Instrumental Variable (IV) approach.FindingsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Similar results were found by Dermendzhieva (2009), Murakami et al (2021), Petreski et al (2019), Al-Assaf (2016), Dey (2022) , Arouri and Nguyen (2018), and Rodriguez and Tiongson (2001) for countries such as Albania, Tajikistan, Macedonia, Jordan, India, Egypt and Philippines, respectively, where the labour supply of the members left behind was reduced. In some countries, the effect is concentrated in men (Albania and rural India) while in others it is more common in women (Macedonia and Philippines).…”
Section: International Evidencesupporting
confidence: 80%
“…Similar results were found by Dermendzhieva (2009), Murakami et al (2021), Petreski et al (2019), Al-Assaf (2016), Dey (2022) , Arouri and Nguyen (2018), and Rodriguez and Tiongson (2001) for countries such as Albania, Tajikistan, Macedonia, Jordan, India, Egypt and Philippines, respectively, where the labour supply of the members left behind was reduced. In some countries, the effect is concentrated in men (Albania and rural India) while in others it is more common in women (Macedonia and Philippines).…”
Section: International Evidencesupporting
confidence: 80%
“…An increased rate of globalization is associated with unemployment due to its social and economic effects [4]. While the impact of migration on the economy has been addressed extensively in economics and politics [5,6], there is still no consensus on the impact of immigration on the labor market [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[19] revealed that migration and emigration positively impact unemployment, especially youth unemployment. Our literature review indicates that this important relationship has largely been ignored in the current literature for the Asia region [7,20].…”
Section: Introductionmentioning
confidence: 99%